MANAGEMENT OF SALMONELLOSIS IN REPTILES: THERAPEUTIC APPROACHES - Cavalcante, Átila Bonfim Ferreira; dos Santos, Erica Nunes; Pissanelli, Isadora Soares; Rodrigues, Lucas de Oliveira; Pereira, Luiza Vaucher Mendes; Lopes, Eduarda de Matos; Pacheco, Davi Victal; Ramos, Camila Soares (Seven Editora, 2026)
This study is characterized as a narrative literature review aimed at compiling and discussing the most recent scientific evidence on the management and therapeutic approaches to salmonellosis in reptiles. Salmonella spp. is the second most common zoonotic agent, and reptiles are asymptomatic natural reservoirs, representing a public health challenge (Reptile-Associated Salmonellosis – RAS). Clinical manifestations in reptiles are nonspecific and variable. Management is hindered by the growing antimicrobial multidrug resistance observed (especially to sulfonamides and aminoglycosides), although resistance to last-resort drugs such as colistin remains low. The therapeutic approach should be cautious, individualized, and, whenever possible, guided by culture and antimicrobial susceptibility testing, focusing on clinical control and mitigation of zoonotic risk rather than complete eradication of the agent, which is considered unlikely. Non-pharmacological strategies, such as strict hygiene, owner education, and quarantine, are crucial. The findings reinforce the importance of a “One Health” approach and the role of reptiles as environmental sentinels in the circulation of strains with zoonotic potential.